E3 ubiquitin ligase Smurf2: a prognostic factor in microsatellite stable colorectal cancer - Klupp, Fee; Giese, Christina; Halama, Niels; Franz, Clemens; Lasitschka, Felix; Warth, Arne; Schmidt, Thomas; Kloor, Matthias; Ulrich, Alexis; Schneider, Martin (Cancer management and research, 2019)
E3 ubiquitin ligase Smurf2: a prognostic factor in microsatellite stable colorectal cancer
Gesehen am 09.10.2019